"Lots of Questions about 'Fake News'": How Public Libraries Have Addressed Media Literacy, 2016–2018. Issue 4 (2nd October 2019) - LaPierre, Suzanne S.; Kitzie, Vanessa
ABSTRACT: This exploratory research investigates how American public libraries have addressed the issue of media literacy in their communities from 2016 to 2018, including programs, partnerships, and other initiatives. The authors selected this period because events, such as the 2016 U.S. presidential election, contributed to an increased national concern about media literacy. This study fills a research gap by providing a broader assessment of public library responses to this issue, as most of the published literature thus far stems from academic libraries. An electronic survey solicited data from both a stratified purposive sample and a self-selecting sample of public libraries throughout the United States (U.S.). Analysis of qualitative and quantitative data from sixty-five public libraries revealed several key themes related to media literacy initiatives, including types of initiatives developed, initiatives deemed most successful by staff, community response to initiatives, and reasons for not pursuing initiatives. Findings denote the current state of how public libraries address media literacy and offer practical guidance for those developing media literacy initiatives. Key findings are as follows: lack of staff time is the reason most often cited for not engaging in media literacy initiatives; more effective measurements are needed to assess both community needs and outcomes of library initiatives; "fake news" is a topic of interest in the community and among library staff; and there appears to be a relationship between staff interest in the topic and perceived interest on the part of the public, which may impact efforts to address the issue. Implications for practice resulting from those findings include engaging in initiatives that maximize service while minimizing staff time involvement; measuring and assessing community interests as well as outcomes of initiatives; using trending topics such as "fake news" to increase interest in library services; and continuing to increase staff awareness of and training in issues deemed important by the library community.